The impact of psycho-education on school-children's homophobic attitudes. (19th May 2022) - Iuso, Salvatore; Petito, Annamaria; Ventriglio, Antonio; Severo, Melania; Bellomo, Antonello; Limone, Pierpaolo
Abstract: Homophobic bullying is a major social issue, especially in the school settings. This may be particularly common in many Western countries but it appears globally. Bullying causes both short and long-term problems hence its prevention must be seen as a relevant and urgent step in educational settings. Psycho-educational programs should be promoted in order to help eliminate school-children's prejudices and bias about gay and lesbian peers, homophobic bullying. 191 school-children ( n = 101 females, n = 90 males), aged 12–14 years old, attending a secondary school in Foggia (Italy) were recruited and assessed at baseline (T0) and 2 months (T1) after receiving a systematized, repeated psycho-education aimed to promote their awareness on sexual variations, and reduce homophobic prejudices and stereotypes. They were assessed for their empathy quotients, their knowledge of gender– related stereotypes, homophobic attitudes, anger, emotional regulation, before (T0) and after the intervention (T1) in a standardized manner. The psychoeducational program significantly reduced homophobia levels towards gays (−9.38%) and lesbians (−5.42%, ) as well as improved emotional adjustment (+25.9%) and pro-sociality (+3.85%) among school-children (0.0486≤ all p < 0.0001). Also, a statistically significant improvement of empathy (+11.3%) and levels of state anger (+0.35%) has been significantly reported. This study reports on the benefits of a repeated, systematic, prospective psycho-educational intervention conducted in the school-setting leading to an improvement of empathy, pro-sociality, emotional regulation and a reduction of homophobic attitudes and anger among students.